Events supposedly attributable to COVID-19 vaccination in children from a family health strategy - Sheila Ilda Eler Mourão; Cláudio Luiz Ferreira Júnior; Leandro Pinheiro Cintra; Josiane Moreira da Costa; Renata Aline de Andrade (O Mundo da Saúde)
COVID-19 in children can progress to more severe forms of the disease, such as severe acute respiratory syndrome and pediatric multisystem inflammatory syndrome. This study aimed to analyze Events Supposedly Attributable to Vaccination or Immunization (ESAVI) in the pediatric population. It was an exploratory, cross-sectional, and retrospective study conducted in the municipality of Conceição do Mato Dentro. Data were collected via telephone for 260 children vaccinated between January and July 2022 using the Ministry of Health's adverse events investigation form associated with the use of vaccines, serums, or immunoglobulin. Microarea 1 had the highest occurrence of ESAVI (4.23%); local pain was reported by 8.08% of vaccinated individuals, and Black children were 6.29 times more likely to present ESAVI. Promoting vaccine safety for COVID-19 has a crucial role in maintaining vaccination coverage rates and reducing illness rates.